THE INFLUENCE OF CONSUMPTION LEVELS, INFLATION, CAR, AND BOPO AGAINST PROBLEM FINANCING IN SHARIA COMMERCIAL BANK - Amima, Alda Fildza; Khoiriyah, Rahmawati; Shamsuddin, Muhammad Aiman Hakim Bin (Universitas Muhammadiyah Prof DR HAMKA, 2024)
The aim of this research is to identify variables that influence Non-Performing Financing (NPF) of sharia banking in Indonesia. Consumption level (GDP), price increase (inflation), capital adequacy (CAR), operating expenses and operating income (BOPO) are the variables used in this research as independent variables. This data was taken from the Sharia Financial Development Report and analyzed using the multiple regression method. The general population in this research is Sharia Commercial Banks registered with the Financial Services Authority (OJK) in 2018-2022, with a total research observation sample of 5 types of Sharia banks, because other categories of Sharia commercial banks do not meet the criteria for this research. The research results show that all variables do not have a significant influence on Non-Performing Financing (NPF) except that the Capital Adequacy Ratio (CAR) has a small influence on Non-Performing Financing (NPF). Previous research explains that capital adequacy (CAR) has a positive and significant effect on non-performing financing (NPF). Meanwhile, this research explains that capital adequacy (CAR) has a negative effect on non-performing financing (NPF).